Classes on paper and in social reality: A systematization of Bourdieu's perspective on social classes - Seid, Gonzalo (2021)
This article systematizes Pierre Bourdieu's theoretical perspective on social classes. We expose his criticisms to the objectivist and subjectivist points of view in social theory, the foundations of his own proposal, the concept of class habitus, and the struggles of classifications through which classes are constituted.